Menguatkan identitas nasional indonesia di tengah dinamika globalisasi dan keberagaman budaya - Bisyauqillah, Muhammad Althof Muwafffaq (Maliki Interdisciplinary Journal, 2025)
National identity is the main foundation in building the unity and pride of a nation, especially for a country like Indonesia which has a very rich cultural diversity. In the midst of the ever-growing tide of globalization, the challenge of maintaining national identity is getting bigger, given the influence of foreign cultures that can obscure local values. Rapid globalization affects people's mindsets, lifestyles, and preferences, often causing changes in cultural patterns that have long been inherent in Indonesian society. This article aims to examine the role of Indonesian national identity in strengthening a sense of national unity, as well as dealing with the dynamics of globalization and existing cultural diversity. Using a qualitative approach, this study reviews the concept of national identity, its functions as a unifying and differentiating tool, and the challenges faced in maintaining this identity. The results showed that Indonesia's national identity, as reflected in the Pancasila, the Indonesian language, and state symbols, serves as an effective unifying force in maintaining social stability. However, the influence of globalization and foreign cultures can threaten its sustainability, requiring strengthening through national education, promotion of local culture, and increased use of national symbols in everyday life to reinforce a sense of nationality amid diversity.